Odprto ovalno okno - Zaletel, Marjan (Zdravniški vestnik, 2006)
Background. Stroke is the third cause of mortality and leading cause of disability regarding the World Health Organization data. Cryptogenic stroke encompasses 40% of young adults with ischemic stroke. The relationship betweenpatent foramen ovale and cryptogenic stroke has been established in patients younger than 55 years. Furthermore, stronger correlation was found between ischemic stroke and patent foramen ovale in patients with atrial septum aneurysm. patency of foramen ovale can be demonstrated using echocardiography. Transesophageal echocardiography is superior to transthoracic approach because the transducer is very close to the heart and there is less interference with the ultrasound beam. Gold standard in diagnosis of patent foramen ovale is contrast echocardiography with the transesophageal approach. Transcranial Doppler can be used to detect right to left shunt. Studies have shown that transcranial Doppler using echo contrast medium can be used for screening of patents with patent foramen ovale. Antiplatelet therapy is appropriate treatment for patients with patent foramenovale who suffered from cryptogenic stroke. Anticoagulant treatment is justified when additional indication for such therapy exists like atrial septum aneurysm. Percutaneous closure of foramen ovale is a new method for secondary stroke prevention with no conclusive data on its effectiveness. Studies on percutaneous closure are still ongoing. In secondary stroke prevention percutaneous closure has to be done without residual shunt.
Keywords: Adult; Cerebral Infarction; Diagnosis; diagnostika; Echocardiography; Ehokardiografija; Etiology; heart; Heart Septal Defects, Atrial; možganska kap; Možganski infarkt; Odrasli; preventivna medicina; srce; Srce, pretin, defekti preddvorni; srčne hibe; Therapy; Ultrasonografija dopplerska, transkranialna; Ultrasonography, Doppler, Transcranial